Integrasi Multidisiplin di Sekolah Dasar: Pengembangan Pembelajaran Holistik untuk Anak-Anak - Muliyadi; Habibah Nahdatul Zannah (Interdisciplinary Explorations in Research Journal, 2023)
Abstract Multidisciplinary integration at the elementary school level is key in developing holistic learning for students. The application of mathematics in science enables problem solving, measurement, and understanding patterns. The integrative thematic approach combines science and social studies lessons, providing complete meaning for students. Language skills also support understanding of natural science by understanding verbal and written language and their use in achieving certain goals. Art and mathematics are integrated through various creativity, such as using fine arts, music or dance to understand mathematical concepts. The integration of sports in elementary school learning provides benefits in improving students' fitness, concentration, social skills and emotional management. Combining linguistics with mathematics in daily activities in elementary school can be done through an ethnomathematics approach, which links mathematical concepts to students' daily lives. Keywords: Elementary school, Mathematics in science, Language skills in science Abstrak Integrasi multidisiplin di tingkat sekolah dasar menjadi kunci dalam pengembangan pembelajaran holistik bagi siswa. Penerapan ilmu matematika dalam ilmu sains memungkinkan pemecahan masalah, pengukuran, dan pemahaman pola. Pendekatan tematik integratif menggabungkan pelajaran IPA dan IPS, memberikan makna yang utuh bagi siswa. Keterampilan bahasa turut mendukung pemahaman ilmu pengetahuan alam dengan memahami bahasa verbal, tulisan, dan penggunaannya dalam mencapai tujuan tertentu. Seni dan matematika terintegrasi melalui berbagai kreativitas, seperti memanfaatkan seni rupa, musik, atau tari untuk memahami konsep-konsep matematika. Integrasi olahraga dalam pembelajaran di SD memberikan manfaat dalam meningkatkan kebugaran, konsentrasi, keterampilan sosial, serta manajemen emosi siswa. Penggabungan ilmu bahasa dengan matematika dalam kegiatan sehari-hari di SD dapat dilakukan melalui pendekatan etnomatematika, yang mengaitkan konsep matematika dengan kehidupan sehari-hari siswa. Kata kunci: Sekolah dasar, Ilmu matematika dalam sains, Keterampilan bahasa dalam IPA